2020
DOI: 10.3390/ma13081922
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Pool Boiling Heat Transfer Performance Using Tungsten Oxide WO3 Nanomaterial-Based Water Nanofluids

Abstract: This study aims to experimentally investigate the pool boiling heat transfer coefficient behavior using tungsten oxide-based deionized water nanofluids and comparing them to deionized water as conventional fluid. The influence of different dilute volumetric concentrations (0.005%–0.05% Vol.) and applied heat fluxes were examined to see the effect of these parameters on the pool boiling heat transfer performance using nanofluids from a typical horizontal heated copper tube at atmospheric pressure conditions. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The curves shifted to the left side of the boiling curve of water due to nanoparticle addition in it. The shifting of curves signifies that nanoparticle addition leads to an increase in heat transfer for identical superheat temperature [ 42 , 43 ]. Therefore, the heater performance increased.…”
Section: Resultsmentioning
confidence: 99%
“…The curves shifted to the left side of the boiling curve of water due to nanoparticle addition in it. The shifting of curves signifies that nanoparticle addition leads to an increase in heat transfer for identical superheat temperature [ 42 , 43 ]. Therefore, the heater performance increased.…”
Section: Resultsmentioning
confidence: 99%
“…Kamel et al [15] experimentally investigated the performance of pool boiling heat transfer by using tungsten oxide WO3 nanomaterial-based deionized water nanofluids. They made WO3-based water nanofluids by using twostep process.…”
Section: Nanofluids Enhancement On Boilingmentioning
confidence: 99%
“…Figure9: Different boiling phenomena for WO3-based water nanofluids at different volume fractions[15] …”
mentioning
confidence: 99%
“…It was observed that by increasing the volumetric concentration from 0.01% to 0.1%, the nucleate boiling curves shifted towards right due to nanoparticle deposition leading to enhanced capillary action. [14] conducted the pool boiling experiments of tungsten oxide water-based nanofluid with volumetric concentrations of 0.005%, 0.01%, and 0.05% on horizontal copper tube. It was observed that by increasing the applied heat flux, the nucleate boiling heat transfer coefficient increases.…”
Section: Introductionmentioning
confidence: 99%